PENGARUH PENGETAHUAN IBU DAN SIKAP TERHADAP PENCEGAHAN DIARE PADA BALITA DI DUSUN SISWO MULIO TIMUR DESA KWALA BEGUMIT STABAT KABUPATEN LANGKAT - Nixson Manurung (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2022)
Diarrhea is a condition in which a person suffers from loose stools, watery stools, can be mixed with blood and mucus, sometimes accompanied by vomiting. Diarrhea is still the biggest cause of death for children under five years old in the world. According to the United Nations International Child's Emergency Fund (UNICEF), every second one toddler dies of diarrhea, Ridwan Amiruddin, (2007). In carrying out her role as a mother, it cannot be separated from the knowledge relationship she has. the knowledge possessed by the mother, the diarrhea prevention actions taken in toddlers will make the toddlers recover and be healthy. So that toddlers who suffer from diarrhea are handled well and do not cause complications due to diarrhea they experience. The purpose of this study was to determine the relationship between mother's knowledge and attitudes towards preventing diarrhea in toddlers in Siswo Mulio, Kwala Begumit Langkat. This type of research uses the type of research that is analytic observation with a cross sectional research design. The total sampling used in this study was 34 mothers who have toddlers. The data analysis technique carried out by the researcher was a closed questionnaire to the respondents as many as 24 questions, namely 12 questions for the independent variable and 12 questions for the dependent variable, then the variable answer interval was formulated using the Sturgers formula. The results showed that of the 34 mothers who became respondents, the level of knowledge of the respondents was good amounted to 11 people (32.4%), sufficient level of knowledge amounted to 17 people (50%) and the level of poor knowledge amounted to 6 people (17.6%). Based on the attitude of the respondents to the prevention of diarrhea in toddlers, there were 8 good (23.5%), moderate 23 people (67.6%), and 3 bad people (8.8%). The results of the research analysis that has been carried out show that the majority of respondents have sufficient knowledge as many as 17 people (50%) and the majority have sufficient attitudes as many as 23 people (67.6%) and the number of respondents with poor knowledge is 6 people (17.6%) with bad attitudes as many as 3 people (8.8%). Statistical test results obtained p = 0.001 stating that there is a relationship between maternal knowledge and attitudes towards prevention of diarrhea in toddlers in Siswo Mulio Timur Hamlet, Kwala Begumit Village, Stabat District, Langkat Regency with p = 0.001. The mother's role in implementing and preventing diarrhea requires knowledge, because knowledge is one of the components of an important predisposing factor.